A Universal Platform for Fabricating Organic Electrochemical Devices. (31st May 2018) - Duong, Duc T.; Tuchman, Yaakov; Chakthranont, Pong; Cavassin, Priscila; Colucci, Renan; Jaramillo, Thomas F.; Salleo, Alberto; Faria, Gregório C.
Abstract: A general method and accompanying guidelines for fabricating both nonaqueous and aqueous based organic electrochemical devices (OECTs) using water‐insoluble hydrophobic semiconducting polymers are presented. By taking advantage of the interactions of semiconducting polymers in certain organic solvents and the formation of a stable liquid‐liquid interface between such solvents and water, OECTs with high transconductance, ON/OFF ratios of up to 10 6, and enhancements in stability are successfully fabricated. Additionally, key fundamental properties are extracted of both the device and the active channel materials, including the volumetric capacitance and the intrinsic hole mobility. The device architecture and basic principles presented herein are expected to apply to all semiconducting polymers and enable the use in organic bioelectronics of thousands of water‐insoluble materials that have been developed over the last several decades for traditional thin film electronics. Furthermore, the fabrication of low‐powered organic electrochemical artificial synapses is demonstrated. Abstract : In this manuscript, a general method and an accompanying set of guidelines for building aqueous organic electrochemical devices with water‐insoluble semiconducting polymers are provided . By taking advantage of immiscible solvents with compatible solubility parameters, stable, high‐performance organic electrochemical transistors and low‐powered neuromorphic artificial synapses are fabricated that operate in aqueous environments.